Photorespiration in eelgrass (Zostera marina L.): A photoprotection mechanism for survival in a CO2-limited world - Celebi-Ergin, Billur; Zimmerman, Richard C.; Hill, Victoria J. (Frontiers in Plant Science, 2022)
Photorespiration, commonly viewed as a loss in photosynthetic productivity of C3 plants, is expected to decline with increasing atmospheric CO2, even though photorespiration plays an important role in the oxidative stress responses. This study aimed to quantify the role of photorespiration and alternative photoprotection mechanisms in Zostera marina L. (eelgrass), a carbon-limited marine C3 plant, in response to ocean acidification. Plants were grown in controlled outdoor aquaria at different [CO2]aq ranging from ~55 (ambient) to ~2121 μM for 13 months and compared for differences in leaf photochemistry by simultaneous measurements of O2 flux and variable fluorescence. At ambient [CO2], photosynthesis was carbon limited and the excess photon absorption was diverted both to photorespiration and non-photochemical quenching (NPQ). The dynamic range of NPQ regulation in ambient grown plants, in response to instantaneous changes in [CO2]aq, suggested considerable tolerance for fluctuating environmental conditions. However, 60 to 80% of maximum photosynthetic capacity of ambient plants was diverted to photorespiration resulting in limited carbon fixation. The photosynthesis to respiration ratio (PE:RD) of ambient grown plants increased 6-fold when measured under high CO2 because photorespiration was virtually suppressed. Plants acclimated to high CO2 maintained 4-fold higher PE:RD than ambient grown plants as a result of a 60% reduction in photorespiration. The O2 production efficiency per unit chlorophyll was not affected by the CO2 environment in which the plants were grown. Yet, CO2 enrichment decreased the light level to initiate NPQ activity and downregulated the biomass specific pigment content by 50% and area specific pigment content by 30%. Thus, phenotypic acclimation to ocean carbonation in eelgrass, indicating the coupling between the regulation of photosynthetic structure and metabolic carbon demands, involved the downregulation of light harvesting by the photosynthetic apparatus, a reduction in the role of photorespiration and an increase in the role of NPQ in photoprotection. The quasi-mechanistic model developed in this study permits integration of photosynthetic and morphological acclimation to ocean carbonation into seagrass productivity models, by adjusting the limits of the photosynthetic parameters based on substrate availability and physiological capacity.